0323 Workplace Psychosocial Risk Factors for Carpal Tunnel Syndrome: A Pooled Prospective Study0323 Workplace Psychosocial Risk Factors for Carpal Tunnel Syndrome: A Pooled Prospective Study. (23rd June 2014) - Harris Adamson, Carisa; Eisen, Ellen; Hegman, Kurt; Thiese, Matthew; Silverstein, Barbara; Bao, Stephen; Garg, Arun; Kapellusch, Jay; Burt, Susan; Gerr, Fred; Merlino, Linda; Marie Dale, Ann; et al.
Abstract : Objectives: Seven research groups conducted coordinated studies of carpal tunnel syndrome (CTS). In this analysis of the pooled cohort, we estimate associations of workplace psychosocial factors and CTS incidence with adjustment for biomechanical factors. Method: 3515 workers were followed up to 7 years. Case criteria included symptoms consistent with CTS and an abnormal electrodiagnostic study. Psychosocial exposure was measured using the Job Content Questionnaire to assess risk among those with high job strain measures. Individual level occupational biomechanical exposures included the%time spent >30° wrist extension, % time in >30° wrist flexion, total repetition rate, and the%time spent in forceful exertion (>1kg-pinch; >4kg-grip). A sub-cohort of 1091 participants had both psychosocial and biomechanical exposure data. Adjusted hazard ratios were estimated using Cox proportional hazards models. Results: After adjustment for gender, age and BMI in the sub-cohort, high job strain (HR=1.40; 95% CI:0.86–2.28) and high psychological demand (HR=1.25; 95% CI:0.79–1.98) showed statistically non-significant elevation in risk of CTS, and high decision latitude (HR=0.70; 95% CI:0.44–1.13) showed non-significant decrease in risk. When the same models were adjusted for biomechanical exposures, confounding was not evident; the primary exposure effect estimates changed between 1–7% for high job strain (HR=1.30; 95% CI:0.81–2.17), high psychological demand (HR=1.17; 95% CI:0.74–1.83), and high decision latitude (HR=0.71; 95% CI:0.43–1.18). Conclusions: For this sub-cohort analysis, adjustment for biomechanical exposures did not alter the associations between workplace psychosocial factors and incident CTS. The findings suggest that workplace psychosocial risk is independent of workplace biomechanical risk.